2001
DOI: 10.1210/endo.142.9.8377
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of the Sodium/Iodide Symporter Is Up-Regulated in the Thyroid of Fetuses of Iodine-Deficient Rats

Abstract: Is the fetal thyroid already capable to increase its iodide uptake in response to iodine deficiency? To answer this question, we analyzed the expression of the Na(+)/I(-) symporter and several other genes in the thyroid of rat fetuses at 21 d of gestation from control mothers presenting a mild or more severe iodine deficiency. Female rats were placed on a low iodine diet, not supplemented, or supplemented with iodide or perchlorate for 3 months. The maternal and fetal thyroidal iodide uptake was measured 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
0
15
2
Order By: Relevance
“…Although the distribution of NIS in the MP and the FP is not yet known in the literature, a previous study conducted on rats found NIS expression in the fetal side of placenta, but, different from our study, not in the maternal side [9]. This discrepancy between the two studies might be related to different methodologies used in these works, as immunostaining methods were used by Schroder-van der Elst et al [9]. As mentioned above, NIS expression was not detected in the different surfaces of the placenta or the amniotic membrane in some cases even though genetic material was obtained.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the distribution of NIS in the MP and the FP is not yet known in the literature, a previous study conducted on rats found NIS expression in the fetal side of placenta, but, different from our study, not in the maternal side [9]. This discrepancy between the two studies might be related to different methodologies used in these works, as immunostaining methods were used by Schroder-van der Elst et al [9]. As mentioned above, NIS expression was not detected in the different surfaces of the placenta or the amniotic membrane in some cases even though genetic material was obtained.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study concluded that the NIS in the amniotic membrane may contribute to iodine transmission from the mother to the fetus. Although the distribution of NIS in the MP and the FP is not yet known in the literature, a previous study conducted on rats found NIS expression in the fetal side of placenta, but, different from our study, not in the maternal side [9]. This discrepancy between the two studies might be related to different methodologies used in these works, as immunostaining methods were used by Schroder-van der Elst et al [9].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Thyrotropin is the most important regulator of thyroid hormone function. Among other functions, thyrotropin upregulates NIS and TPO [21][22][23]. Because the concentration of thyrotropin was not different between rats fed oxidized fat and those fed fresh fat, it is likely that the effect of the oxidized fat on the thyroid gland was not mediated by thyrotropin.…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of NIS, persuasive evidence suggested that the inhibitory effect of iodide is associated with a decrease in NIS mRNA and protein levels, subsequently reducing iodide transport to the thyroid (Eng, et al 1999;Eng PH 2001;Glatt, et al 2005). In iodine deficient rats, NIS mRNA is up regulated in fetal thyroid, as well as in the placenta (Schroder-van der Elst, et al 2001). In BeWo cells iodide also caused a significant decrease in NIS mRNA and apical membrane protein, followed by a decrease in levels of iodide uptake (Li et al 2007).…”
Section: Regulation Of Placental Iodide Transportmentioning
confidence: 99%